Unveiling Consumer Choices: Navigating Tupperware's Market in Cimahi City - The Dynamic Interplay of Perceived Value, Price, and Brand Image on Repurchase Intentions, Mediated by Customer Satisfaction in the Era of Evolving Trends - Zain, Nabilla Fawwaz; Putra, Hariyadi Triwahyu (J-MAS (Jurnal Manajemen dan Sains), 2024)
This research aims to analyze the impact of perceived value, price and brand image on repurchase intention, mediated by customer satisfaction in the Tupperware product market in Cimahi City amidst developing consumer trends. Using a quantitative approach, data was collected through surveys from Tupperware consumers in Cimahi City. The results of statistical analysis show that there is a significant relationship between perceived value, price and brand image and repurchase intention. Customer satisfaction has also been proven to mediate the relationship between independent variables and repurchase intention. These findings provide in-depth insight into the factors that influence consumer purchasing decisions in the context of Tupperware products. Managerial implications and future research directions are also discussed. This study is expected to help companies optimize marketing strategies and increase customer loyalty in the face of continuously developing market dynamics.